Cryo-EM structure of an activated GPR4–Gs signaling complex - Yitong Ma; Yijie Wang; Mengyuan Tang; Yuan Weng; Ying Chen; Yueming Xu; Shuxiao An; Yiran Wu; Suwen Zhao; Huanhuan Xu; Dali Li; Mingyao Liu; et al. (Nature Communications)
Abstract G protein-coupled receptor 4 (GPR4) belongs to the subfamily of proton-sensing GPCRs (psGPCRs), which detect pH changes in extracellular environment and regulate diverse physiological responses. GPR4 was found to be overactivated in acidic tumor microenvironment as well as inflammation sites, with a triad of acidic residues within the transmembrane domain identified as crucial for proton sensing. However, the 3D structure remains unknown, and the roles of other conserved residues within psGPCRs are not well understood. Here we report cryo-electron microscopy (cryo-EM) structures of active zebrafish GPR4 at both pH 6.5 and 8.5, each highlighting a distribution of histidine and acidic residues at the extracellular region. Cell-based assays show that these ionizable residues moderately influence the proton-sensing capacity of zebrafish GPR4, compared to the more significant effects of the triad residues. Furthermore, we reveal a cluster of aromatic residues within the orthosteric pocket that may propagate the signaling to the intercellular region via repacking the aromatic patch at the central region. This study provides a framework for future signaling and functional investigation of psGPCRs.